Facilitators and barriers to engaging in expressive writing among health and social care professionals - Michael A. Smith; Lauren M. Hoult; Daniel Rippon; Nicola O’Brien; Dawn Branley-Bell; Lucie Byrne-Davis; Caitriona Collins; Stephen Gallagher; Gail Kinman; Arron Mark; Daryl B. O’Connor; Kavita Vedhara; et al. (PLoS ONE, 2025)
Healthcare workers in the UK report high levels of burnout and poor wellbeing, and interventions are urgently needed to address this issue. Expressive writing, whereby individuals write about emotionally laden thoughts or experiences, is an effective intervention for reducing stress and enhancing wellbeing, and is a potential candidate for use with healthcare workers. However, it is crucial that the preferences of healthcare workers are taken into account in the design of future trials in this area, and that perceived barriers and facilitators to engaging with expressive writing activities are considered. Therefore, the present study aimed to seek healthcare workers’ views on expressive writing activities for enhancing wellbeing. We informed 11 UK-based health and social care professionals about current research into the potential wellbeing benefits of expressive writing activities and conducted 1:1 semi-structured interviews to determine their preferences, perceived facilitators and barriers to engaging routinely with expressive writing. Data were analysed using deductive, reflective thematic analysis, with the coding framework informed by the Capability-Opportunity-Motivation-Behaviour (COM-B) Model. Key findings, from the perspective of future trial design, were that participants preferred the three good things (writing down three good things that have happened during the day), written benefit finding (writing about positive emotions, thoughts, feelings and life changes in relation to an unfavourable experience) and gratitude letter (writing a letter of appreciation to someone who has never been properly thanked) activities. Participants expressed preferences for simple, brief activities that could be easily embedded into a daily routine. However, it was clear that support from managers, researchers or friends and family would be needed to promote engagement with the activities. Most notably, participants expressed a preference for flexibility in terms of how, when and where they write.